GEN-SMART DIGITAL MEDIA: AN ADDIE-BASED DEVELOPMENT TO IMPROVE LEARNING MOTIVATION IN SOCIAL STUDIES - Achmad Dhohirrobbi; Luthfiya Fathi Pusposari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study develops and evaluates the feasibility and effectiveness of the Gen-Smart digital learning media in enhancing learning motivation among lower secondary Social Studies students. The research adopts a Research and Development (R&D) approach utilizing the ADDIE framework, consisting of analysis, design, development, implementation, and evaluation stages. Gen-Smart was designed using Canva AI, Google Sites, and Website2APK Builder Pro to ensure multi-platform access. Feasibility was evaluated through expert validation and student practicality surveys, while effectiveness was measured using pre-test and post-test scores analyzed with normalized gain (N-Gain). The results indicate a high feasibility level, with validation scores of 92% from the material expert and 89% from the media expert. Student practicality responses reached 83%, categorized as